Comparison between cimetidine and Caved-S in the treatment of gastric ulceration, and subsequent maintenance therapy. Issue 6 (June 1982) - Morgan, A G; McAdam, W A; Pacsoo, C; Darnborough, A
Abstract : One hundred patients with benign gastric ulceration were treated in a single-blind, endoscopically controlled trial to assess the relative efficacy of cimetidine (1 g daily) and Caved-S (six tablets daily). Ulcer healing was assessed after six weeks' treatment, and, if incomplete, after a further six weeks. There was no significant difference between the two drug regimens (approximately 63% at six weeks and 91% at 12 weeks). If an ulcer remains unhealed after 10 weeks' treatment the patient should undergo surgery. There was no difference in the relief of day pain between the two drug regimens but cimetidine was more effective over the first two weeks of treatment relieving night pain, than was Caved-S (p less than 0 . 02). After ulcer healing, drug dosage was reduced (cimetidine to 400 mg at night and Caved-S to two tablets twice daily). So far, 56 patients, 28 in each group, have completed the first year's maintenance treatment, and there have been four ulcer recurrences in each group (14%).